Partial characterization of the venom of the Peruvian rattlesnake Crotalus durissus terrificus - Remuzgo, César (2000)
The venom of the rattlesnake Crotalus durissus terrificus from the region of Sandia, Puno, has been investigated for its protein content and some enzymatic activities, using for it the whole venom as well as the fractions obtained by gel filtration chromatography in Sephadex G-100. The protein percentage calculated by the method of Lowry was of 68,6% for the whole venom; 3 peaks were obtained during the fractionation; the first showed proteolytic activity, the second, amidolytic, clotting and phospholipase A2 activities, while the third, another proteolytic activity. Acetylcholinesterase activity was not found while L-aminoacid oxidase activity was found only in the whole venom.